PENDEKATAN PEMBELAJARAN KONFLIK KOGNITIF UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA SMA PADA TOPIK SUHU DAN KALOR - Sirait, Judyanto (Universitas Tanjungpura, 2010)
The goal of this research is to obtain the gain of students conceptual understanding in applied cognitive conflict approach in heat and temperature. Method of the research is experiment that conducted at 10th grade in one of senior high school in Bandung. Cognitive conflict approach was used on experiment group while control group used conventional approach. Data were collected through pretest, posttest, questionaire, and observation sheet. Data was analized statistically by t-test. The result showed that normalized gain of conceptual understanding of experiment group and control group 0.57 , 0.35 respectively. It showed that average of normalized gain of experiment group is higher than that of control group significantly. The conclusion of the research was cognitive conflict approach increase students conceptual understanding. Besides that students and teachers responses gave positively.Key words: cognitive conflict, conceptual understanding